EFL Students’ Self-Regulated Learning Strategies during the Covid-19 Pandemic - Hung, Do Minh (Arab world English journal, 2022)
In the current contexts of Vietnam, college students are taking entirely or partially online courses due to the spread of the Covid-19 pandemic. Thus, students should develop and optimally employ self-regulated learning strategies for effective learning outcomes. Research also indicates that self-regulation among students is linked to the 21st century skills. With this in mind, the present study attempts to investigate the self-regulated learning strategies of English-as-a-foreign-language (EFL) students from a local university in Vietnam. The study aims to identify EFL students’ self-regulation level, correlation between their two cognition knowledge and cognition regulation, and the correlation between their self-regulation level and GPA. Data is collected via a survey questionnaire encompassing two core components of cognition knowledge and cognition regulation. The results show a high level of the involved students’ self-regulation, a correlation between their cognition knowledge and cognition regulation, but a gap between their self-regulation level and GPA. On the obtained findings, pedagogical implications are addressed, and further research is suggested.